THYROID STORM IN PREGNANCY - Rima Hayyu Chrisnanda; Sidarti Soehita (Indonesian Association of Clinical Pathologist and Medical laboratory, 2019)
Hyperthyroidism complicating pregnancy is a rare and threatening case. The incidence is about two cases in 1,000 pregnancies. A 33-year-old female, 32-33 weeks pregnant was admitted with shortness of breath since 2 days before hospitalization. She also suffered from vaginal bleeding, headache, nausea and palpitation and was diagnosed with hyperthyroidism since 3 years ago, but the medication was uncontrolled. Physical examination: body temperature 37.7° C, heart rate 170 x/minute, respiratory rate 40 x/minute and blood pressure 150/90 mmHg and no goiter. Laboratory result: Hemoglobin 10.6 g/dL, WBC 2.39 x 103/uL, and albumin 2.8 g/dL, AST 1.162 IU/L, ALT 154 IU/L, FT4 > 30 ng/dL, TSH 0.0008 µIU/mL and T3 6.3 ng/mL, Procalcitonin 8.57 ng/mL and proteinuria + 3. ECG: sinus tachycardia. Burch Wartofsky Score was 55. Blood Gas Analysis: pH 7.13, pCO2 33mmHg, pO2 174 mmHg, HCO3 -11 mmol/L, BEecf -18.2 mmol/L. Chest X-Ray: opacities on both lungs. At the time, her fetus was still alive. She was admitted to the ICU and treated with aggressive medical therapy. On the next day, she lost consciousness and no fetal heart was detected. Decided to induce labor if Burch Wartofsky score < 25. On the third day, the condition was worsened and the next day she passed away due to septic shock. Based on the physical examination and the laboratory results, the patient was diagnosed with thyroid storm with preeclampsia and pneumonia. Uncontrolled maternal hyperthyroidism in pregnancy may cause thyroid storm, IUFD and preeclampsia.